Perjuangan Siti Soendari Darmobroto dalam Memperjuangkan Hak-Hak Perempuan Indonesia, 1913-1914 - Akbar, Farhan; Maryuni, Yuni; Prasadana, Muhammad Anggie Farizqi (Universitas Hamzanwadi, 2024)
Journalism and mass media are widely used by people not only to find out the latest news circulating in society but also as a tool to spread certain ideas and ideas so that they can influence and shape public opinion about a social phenomenon that occurs around them. they. The development of ethical politics in the Dutch East Indies in the half of the 20th century opened the gates to a historical period known as the